(untitled) (Jurnal Teknologi (Sciences & Engineering), 2019)
This research investigates the solution parameters, i.e., polymer concentration and addition of manganese (IV) oxide (MnO2) nanoparticles, for the fabrication of polysulfone (PSF) fibers via electrospinning. Initially, PSF was dissolved in N,N-dimethylformamide (DMF) solvent and electrospun fibers with different morphologies were obtained using the range of PSF concentration of 10% (w/v) to 25% (w/v). Subsequently, PSF with the concentration of 20% (w/v) (denoted as PSF(20%)) was chosen to blend with 0.2% (w/v) of MnO2 as it gave the most stable electrospinnability and uniform fiber diameter. The fabricated electrospun PSF(20%) and PSF(20%)-MnO2 fibrous membranes were characterized to determine the morphology, wettability property, zeta potential, and tensile strength. The presence of MnO2 improved tensile strength as it reduced the fiber diameter that eventually made a more compact fiber mat membrane. The results of contact angle confirmed that the fabricated fiber exhibited more hydrophobic property in the presence of MnO2 nanoparticles. Thus, it reduced the pure water flux of PSF fiber membrane. The more hydrophobic nature of the proposed nanofiber might be useful in enhancing the application of PSF fiber in oil-water separation process.